2010
DOI: 10.1371/journal.pone.0014081
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Hv1 Proton Channel in Human Granulocytes

Abstract: Voltage-gated proton current (IHv) has been characterized in several cell types, but the majority of the data was collected in phagocytes, especially in human granulocytes. The prevailing view about the role of IHv in phagocytes is that it is an essential supporter of the intense and sustained activity of Nox2 (the core enzyme of the phagocyte NADPH oxidase complex) during respiratory burst. Recently Hv1, a voltage-gated proton channel, was cloned, and leukocytes from Hv1 knockout mice display impaired respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 45 publications
1
68
0
1
Order By: Relevance
“…HUVECs from different donors exhibit significant heterogeneity [47]. To reduce further variances in our experiments, we used a DMSO-differentiated PLB-985 cell line -devoid of the heterogeneity of primary cells, which is a well-known and suitable cellular model to study the functional responses of neutrophils [31,48]. Furthermore, dPLB-985 could bind to E-selectin, whereas nondifferentiated PLB-985 could not, and this supports that it could be a suitable model for the assessment of adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs from different donors exhibit significant heterogeneity [47]. To reduce further variances in our experiments, we used a DMSO-differentiated PLB-985 cell line -devoid of the heterogeneity of primary cells, which is a well-known and suitable cellular model to study the functional responses of neutrophils [31,48]. Furthermore, dPLB-985 could bind to E-selectin, whereas nondifferentiated PLB-985 could not, and this supports that it could be a suitable model for the assessment of adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The channel opens with depolarization and activates more rapidly at more positive voltages. In three other species-human, mouse, and C. intestinalis-H V 1 seems to exist as a dimer, in which each monomer contains its own conduction pathway (44,(46)(47)(48). The dimer is held together mainly by coiled-coil interactions in the C terminus (44,46,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated the relationship between the high-affinity LTB 4 receptor, BLT1, and NOX2 in LTB 4 -stimulated eosinophils (34). Although NOX2 generates ROS and NOX2-derived ROS are generally coupled to exocytotic degranulation in human eosinophils stimulated with LTB 4 (64,65), information regarding the functional role of NOX2 in regulating BLT1-mediated exocytotic degranulation in TvSP-stimulated mast cells remains elusive. In this study, we found that TvSP induced phosphorylation of p47 phox and ROS generation in HMC-1 cells (Fig.…”
Section: Discussionmentioning
confidence: 91%